Influence of Customer Value, Commitment and Product Advantage on Customer Satisfaction and Loyalty (Study On the Bahteramas Rural Bank in Southeast Sulawesi) - Ahmat, Ahmat (International Journal of Management and Education in Human Development, 2021)
This study aims to determine the effect of customer value, customer commitment to product excellence on customer satisfaction and customer loyalty at the Bahteramas Rural Bank, Southeast Sulawesi. This study used a sample of 123 respondents. The analytical technique used is descriptive statistical analysis technique, and inferential statistics. The analytical tool used is Structural Equation Modeling (SEM) using the SPSS Ver program package. 18.0. The results showed that; Customer value has positive and significant effect on customer satisfaction; Customer commitment has a positive and significant effect on customer satisfaction: Product excellence has a positive and significant effect on customer satisfaction: Customer value has a positive and significant effect on customer loyalty: Customer commitment has a positive and significant effect on customer loyalty: Product excellence has a positive and significant effect on loyalty and: Satisfaction customer has a positive and significant effect on customer loyalty at the Bahteramas Rural Bank in Southeast Sulawesi.